Rehabilitative Counseling Intervention for Children with Motor Disabilities: A Case Study at SLB - Rodame Samosir; Budi Susetyo; Iding Tarsidi (Mimbar Ilmu, 2026)
The lack of optimal implementation of rehabilitative counseling services in supporting the comprehensive and sustainable psychological and social development of students with motor disabilities is the main problem in this study. This study aims to explore the implementation and impact of rehabilitative counseling in improving the psychosocial well being of students with motor disabilities in special education settings. This research uses a qualitative approach with a case study design involving students with motor disabilities, special education teachers, school counselors, and parents. Data were collected through participatory observation, in-depth interviews, and documentation studies, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing and verification. The results show that rehabilitative counseling, delivered through individual and group services focusing on self acceptance, emotional regulation, and social skills, has a positive impact by increasing students’ self confidence, emotional openness, and social participation. The biopsychosocial approach and client-centered counseling have proven effective in supporting students’ psychosocial well-being, while collaboration between counselors, teachers, and parents plays an important role in ensuring service sustainability. The conclusion indicates that structured and collaborative rehabilitative counseling is effective in improving the psychosocial well-being of students with motor disabilities, while the implication emphasizes strengthening integrated services, improving educators’ competencies, and optimizing collaboration between schools and parents.